Examination of Bacterial and Archaeal Populations in Salt, Salted and Soaked Hide and Soak Liquors via Fluorescent In Situ Hybridization - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2010)
A high bacterial population belonging to the domains of Bacteria and Archaea originating from inadequate salt curing and soaking processes may cause an important quality reduction in leather A simple and rapid molecular technique such as Fluorescent In Situ Hybridization technique (FISH) which may be applied in leather making processes may assist to solve this problem Therefore, in the present study the FISH technique was used to track Bacterial and Archaeal domains in salt (n=15), salted (n=15) soaked hides (n=15) and soak liquor (n=15) samples Although Archaeal population was dominant in the salt samples, a Bacterial population was dominant in the soaked hide and soak liquor samples The salted hide samples contained both Archaeal and Bacteria/populations The FISH method applied to the samples showed that high extremely halophilic Archaeal population on the salted hides and high Bacterial population in soak liquors and soaked hides originated from the salt and the salted hides, respectively As a conclusion, the FISH technique was found suitable for the rapid assesment and tracking microbial domains in salt, salted and soaked hide and soak liquor samples
Keywords: COMMUNITY STRUCTURE; IDENTIFICATION; MICROORGANISMS; FISH; SOIL; QUALITY; LEATHER; CELLS